ON THE SYMMETRIC *-POLYNOMIALS OF TWO COMPLEX VARIABLES - Василишин, Тарас Васильович; Струтинський, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We show that the every symmetric *-polynomial of two complex variables can be represented as an algebraic combination of the elementary symmetric *-polynomials.